Testing the magnetar scenario for superluminous supernovae with circular polarimetry. Issue 4 (3rd May 2018) - Cikota, Aleksandar; Leloudas, Giorgos; Bulla, Mattia; Inserra, Cosimo; Chen, Ting-Wan; Spyromilio, Jason; Patat, Ferdinando; Cano, Zach; Cikota, Stefan; Coughlin, Michael W; Kankare, Erkki; Lowe, Thomas B; et al.
ABSTRACT: Superluminous supernovae (SLSNe) are at least ∼5 times more luminous than common supernovae. Especially hydrogen-poor SLSN-I are difficult to explain with conventional powering mechanisms. One possible scenario that might explain such luminosities is that SLSNe-I are powered by an internal engine, such as a magnetar or an accreting black hole. Strong magnetic fields or collimated jets can circularly polarize light. In this work, we measured circular polarization of two SLSNe-I with the FOcal Reducer and low dispersion Spectrograph (FORS2) mounted at the ESO's Very Large Telescope. PS17bek, a fast-evolving SLSN-I, was observed around peak, while OGLE16dmu, a slowly evolving SLSN-I, was observed 100 d after maximum. Neither SLSN shows evidence of circularly polarized light; however, these non-detections do not rule out the magnetar scenario as the powering engine for SLSNe-I. We calculate the strength of the magnetic field and the expected circular polarization as a function of distance from the magnetar, which decreases very fast. Additionally, we observed no significant linear polarization for PS17bek at four epochs, suggesting that the photosphere near peak is close to spherical symmetry.